NAVIGATING BARRIERS AND OPPORTUNITIES: THE FUTURE OF BREAKBULK SHIPPING IN KRISTINEHAMN POST-TROLLHÄTTE CANAL LOCKS UPGRADES - Månsson, Fabian; Alexandersson, William (My University, 2024)
Historically, Sweden's inland waterways have been critical for heavy transport of goods. However, the goods flow on lake Vänern has declined gradually since the 1990s. Sweden's geographical layout possesses great potential for utilizing inland transport with coastal ports in Sweden and around Europe. This thesis investigates the impact of the Trollhätte canal locks upgrades on breakbulk cargo shipping in Kristinehamn, focusing on the potential transformation of Sweden's inland waterways as a viable mode of freight transport. The study utilizes a qualitative case study methodology, employing semi-structured interviews with key stakeholders in the maritime and logistics sectors to explore potential barriers and the possible effects of the new locks in the Trollhätte canal. Significant findings suggest that the lock upgrades will likely enhance vessel capacity and operational efficiency, thereby promoting Kristinehamn as a strategic hub. Economically, the upgrades are projected to attract more industrial activities to the region and potentially reduce transportation costs due to increased cargo volumes. Multiple challenges within the shipping of breakbulk to and from Kristinehamn were found. High operational costs, unjust competitiveness against other modes of transport, infrastructural limitations, and regulatory complexity. These barriers inhibit the competitiveness of the breakbulk goods flow.
Keywords: Breakbulk Shipping; Port of Kristinehamn; Trollhätte Canal; Lock Upgrades; Inland Waterway Transport; Shipping Barriers